Estudo sobre a ictiofauna do Rio Cabeça, um tributário do Rio Corumbataí com nascentes nas cuestas basalticas do estado de São Paulo - Cardoso, Rodrigo Torres (2012)
This study investigates the composition and distribution of fish species from Rio Cabeça, a tributary of Rio Corumbataí basin. Fish samples and physical data were monthly collected at four regular sampling sites and during 12 months, thorough the channel of Rio Cabeça and on five additional collection sites. From the physical data, width, depth and water velocity (in m/s) of the river were obtained. The fish collections were made with help of: gill net, trawl net, other hand net and sieve. Species richness and abundance were designed thorough the constancy of occurrence of the species; the Jaccard similarity analysis of rarefaction; the species accumulation curve and a descriptive analysis of the collecting sites. The sampling sites showed physical characteristics as: Site 1, narrow but deep and with rapid waters. Site 2, wider and shallower and with more water spread. Site 3, mostly broad and deeper. Site 4, also broad and shallow, but containing rapids and fast waters. The samples include 4.532 fish specimens belonging to six orders, 17 families and 65 species. Site 4, showed the best richness and abundance, and the other three sites revealed to be more or less similar. In terms of constancy the site 4 had the highest percentage of occasional species, while the other three sites had the highest percentage of regular species. The analysis of rarefaction had shown a greater richness of species at site 4 and lower species richness at remaining sites. The species accumulation curve shown that a considerable proportion of fish species is present in this river as represented in this study. The Jaccard similarity analysis shown significant differences in the species composition through the four collecting sites. The results and the discussion suggest that the basaltic Corumbataí mountain formation may interfere with the distribution, composition and richness of the ichthyofauna. On the other hand, the Rio Cabeça with 65 fish species is an important tributary of the Rio Corumbataí. Finnaly this study outcome the necessity of more attention to ichthyofauna conservation at waterfall environments, where the specimens are exposed to illegal fisheries.